PERUSAHAAN DALAM PERSPEKTIF ISLAM - Djakfar, Muhammad (IQTISHODUNA, 2009)
To live, human beings need to work or have a job, and indeed the kind of work they do depends on their preference based on individuals’ capabilities and skills. Amongst the most sought professions is having a business activity that needs to be properly managed, and bulding  a company becomes one of many ways to make these activities run in  a proper way. Bay having a company ones will understand their right and obligations according to practiced rules. It is the author’s interest to point out that in the present time where shari’ah -based business activities has started to grow many still have little understanding about a company from an Islamic point of view. For a Muslim businessman, as well as Indonesian citizens, should understand the system of enterprise not only in term of national regulation perspective but also in Islamic point of view. For this purpose, this article makes an effort to integrate the discourse about enterprise in Islamic perspective and in national regulation perspective.